Saving the savior: a deconstruction of the Novel Viajero by F. Sionil Jose - Dennis H. Pulido (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2011)
The study ventured to use Derridean deconstruction as a method of analyzing the novel Viajero. It aimed to identify the binary oppositions in the novel, establish the hierarchical relationship existing within each binary opposition, deconstruct the binary opposition, identify the parts of the novel showing the unstable relationship between the terms in the binary opposition, interpret the text and identify the implications of Derridean deconstruction for enhancing the critical reading skills of the learners. Deconstructing the binary oppositions in the novel Viajero by F. Sionil Jose was done primarily through content analysis. This needed a close reading of certain parts of the novel Viajero. Derridean deconstruction was then used to come up with an interpretation of the novel. Much binary opposition exists in Viajero. The interaction of the multitudinous characters and various social constructs produce hierarchical relationships. These binary oppositions privilege one term upon the other. But upon closer reading and investigation, this privileged/less privileged status reveals its inherent instability and inconsistency. Furthermore, the novel contains inherent traces that displace the hierarchical relationship existing between the terms in the binary oppositions. Finally, Derridean deconstruction can be used as a basis for analyzing literary texts